Should we blame COVID-19 for the decline in transit ridership, or was it merely a stimulant? - Helia Mohammadi-Mavi; Mustafa Fardin; Andisheh Ranjbari (Transportation Research Interdisciplinary Perspectives)
Public transit ridership significantly declined during the COVID-19 pandemic and has not yet rebounded, even though the virus substantially subsided and people have mostly returned to their normal lives. This suggests that there are reasons for this drop that go beyond health concerns and work-from-home arrangements. Focusing on pre-pandemic transit users, this study aims at understanding the most influential behavioral and attitudinal reasons for the transit ridership decline. Exploiting a survey dataset from the U.S. Pacific Northwest region, we performed two analyses: structural equation modeling, and user clustering (based on attitudes) combined with statistical tests. The core of both analyses was people’s attitudes/perceptions toward three matters: sharing rides with strangers, doing activities online vs. in person, and pandemic health risks. The results showed that while those three all play a role in post-pandemic reduced transit use frequency, the reluctance to share rides is the only direct and significant factor and that its magnitude is three times larger than the health concerns/fears associated with the pandemic. The latter was found to have rather an indirect effect on reducing transit ridership, through its impact on both ridesharing reluctance and online activities preference. This implies that focusing solely on safety and protective measures will not restore transit ridership to its pre-pandemic levels. Investments may be directed toward improving rider security and comfort and offering discounts or reduced fares. Moreover, given the extended work-from-home activities, it is recommended that transit agencies shift their focus in route planning and service marketing from work trips to other trip purposes.